THE EFFECT OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. PERMODALAN NASIONAL MADANI MEKAAR CABANG JAKARTA - Soemardana, Soemardana; Jati, Prihatina; Astuti, Indri (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
The sampling technique used in this study was the saturated sample technique. then a sample of 100 Employees of PNM Mekar, Jakarta Branch was taken as respondents in this study. There is an effect of Compensation on Employee Performance, as evidenced by the t-count value for the Compensation variable (X1) of 7.003 while the t-table value for N = 100 was 1.983. So 7.003 > 1.983, then H0 is rejected and Ha is accepted, it can be stated that Compensation (X1) has a significant effect on Employee Work Performance (Y). There is an influence of Work Motivation on Employee Work Performance, proven by the t-value for the Work Motivation variable (X2) of 3.788, while the t-table value for N = 100 is 1.983. So 3.788 > 1.983, then H0 is rejected and Ha is accepted, it can be concluded that partially the Work Motivation variable (X2) has an effect on Employee Work Performance (Y). There is an influence of Compensation and Work Motivation together on Employee Work Performance, proven by the results of the ANOVA test obtained an F-value of 51.675 While F-table (a 0.05) for N = 100 is 2.70. So Fcount > from Ftable (a 0.05) or 51.675 > 2.70 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Compensation (X1) and Work Motivation (X2) together have a positive effect on Employee Work Performance (Y). Adjusted R Square (R2) is 0.516. This shows that 51.6% of Compensation (X1) and Work Motivation (X2) simultaneously have an effect on Employee Work Performance (Y) while the remaining 47.4% is influenced by other factors not examined in this study.